The Effect of Tax Planning, Deferred Tax Assets and Deferred Tax Expense on Earnings Management in Consumer Goods Companies Listed on the Indonesia Stock Exchange for 2018-2021 Period - Veren Franio; Juliandi Saputra (Institute of Computer Science (IOCS), 2022)
This study aims to determine the relations between Tax Planning, Deferred Tax Assets and Deffered Tax Expense on Profit Management in consumer goods companies listed on the Indonesia Stock Exchange in the 2018-2021 period. And to find out if there are problems with profit management that affect consumer goods companies listed on the Indonesia Stock Exchange. The methodology used is Multiple Linear Analysis, Coefficient of Determination, T-Test, and F-Test. It is concluded that this research has a significant effect on Tax Planning on Profit Management, while Deferred Tax Assets and Deferred Tax Expense have no effect on profit management. Simultaneously Tax Planning, Deferred Tax Assets and Deferred Tax Expense have a significant effect on profit Management.